Construction of Teaching Materials To Facilitate 21st Century Learning on Critical and Creative Thinking - Sarjana, Ketut; Kurniawan, Eka; Lu'luilmaknun, Ulfa; Kertiyani, Ni Made Intan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to produce teaching materials based on 21st century learning for prospective teacher students that are valid and effective. The method of this research was research and development (R&D) using the Thiagarajan 4D model. This model consists of several stages, namely definition, design, development, and dissemination. The test subjects of this research were 27 third-semester mathematics education students at the University of Mataram. Data was collected using a validation questionnaire for teaching materials for material experts, media, practitioners and lecturer and student response questionnaires. Meanwhile, effectiveness data was obtained from student scores on ability tests at the end of using teaching materials. The data was analyzed descriptively to categorize the classical completeness from the scores. The results of the research showed that the teaching materials for teaching critical and creative thinking skills met the criteria valid according to the assessment of material experts, media experts, practitioner experts, lecturers, and students, and their effectiveness has been tested so that it can be concluded that this module meets the requirements for use in learning to build creative thinking and critical thinking skills. These teaching materials can be references for teachers to study how to stimulate studentâ€™s critical and creative thinking.Â